Finding solutions to Covid-19 squabble in Nigeria: Implications for counseling - Akinduyo, Tosin (Journal of Advanced Guidance and Counseling, 2024)
Purpose - The purpose of this study was to examine solutions to the COVID-19 squabble and implications for counselling. As of 27th December 2021, the number of COVID-19 confirmed cases globally was 279,114,972 and 5,397,580 deaths.Method - This study utilized an integrative review technique that assisted the researcher in reviewing literature from reliable databases. These databases gave genuine information relating to this topic being investigated.Result -  The results showed that solutions were urgently needed to some of the numerous crises that include but are not limited to coronaphobia, inadequate ICT deployment, recession, agoraphobia, insecurity, drug menace, food insecurity, various health concerns, unemployment squabbles created by the deadly COVID-19 pandemic.Implication - This method suggests how to improve on the over-spilling problems created by COVID-19 pandemic to date, and importantly, professional counsellors should be well-funded to actively help defeat the COVID-19-induced squabbles.Originality/Value - This research bolsters up the essence of not defeating COVID-19 variants alone, but as well totally trouncing the scores of COVID-19-instigated squabbles, that are still adversely affecting the globe.***Tujuan - Tujuan dari penelitian ini adalah untuk mengkaji solusi untuk mengatasi COVID-19 dan implikasinya terhadap konseling. Pada 27 Desember 2021, jumlah kasus COVID-19 yang dikonfirmasi secara global adalah 279.114.972 dan 5.397.580 kematian.Metode - Penelitian ini menggunakan teknik tinjauan integratif yang membantu peneliti dalam meninjau literatur dari database yang dapat diandalkan. Basis data ini memberikan informasi asli yang berkaitan dengan topik yang sedang diteliti.Hasil - Hasil penelitian menunjukkan bahwa solusi sangat dibutuhkan untuk beberapa krisis yang mencakup tetapi tidak terbatas pada coronaphobia, penyebaran TIK yang tidak memadai, resesi, agoraphobia, rasa tidak aman, ancaman narkoba, kerawanan pangan, berbagai masalah kesehatan, pertengkaran pengangguran yang disebabkan oleh pandemi COVID-19 yang mematikan.Implikasi - Metode ini menunjukkan bagaimana cara memperbaiki masalah yang berlebihan yang disebabkan oleh pandemi COVID-19 hingga saat ini, dan yang terpenting, konselor profesional harus didanai dengan baik untuk secara aktif membantu mengatasi pertengkaran yang disebabkan oleh COVID-19.Keaslian/Nilai - Penelitian ini memperkuat esensi dari tidak hanya mengalahkan varian COVID-19 saja, tetapi juga secara total mengalahkan jumlah pertengkaran yang dipicu oleh COVID-19, yang masih berdampak buruk pada dunia.